Iron deficiency and anemia: A common problem in female elite soccer players - Landahl, G.; Adolfsson, P.; Börjesson, M.; Mannheimer, C.; Rödjer, S. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
The objective of the study was to determine the prevalence of iron deficiency and iron deficiency anemia among elite women soccer players. Hemoglobin, serum iron, serum total iron binding capacity, and ferritin were determined in 28 female soccer players called up for the national team. Of the investigated female soccer players, 57% had iron deficiency and 29% iron deficiency anemia 6 months before the FIFA Women`s World Cup. It is concluded that iron deficiency and iron deficiency anemia is common in female soccer players at the top international level. Some might suffer from relative anemia and measurement of hemoglobin alone is not sufficient to reveal relative anemia. Regular monitoring of hemoglobin concentration and iron status is necessary to institute iron supplementation when indicated.